Photo-induced copper-catalyzed alkynylation and amination of remote unactivated C(sp3)-H bonds. Issue 13 (23rd February 2021) - Cao, Zhusong; Li, Jianye; Sun, Youwen; Zhang, Hanwen; Mo, Xueling; Cao, Xin; Zhang, Guozhu
Abstract : Remote C−H alkynylation and amination of aliphatic alcohols. Abstract : A method for remote radical C–H alkynylation and amination of diverse aliphatic alcohols has been developed. The reaction features a copper nucleophile complex formed in situ as a photocatalyst, which reduces the silicon-tethered aliphatic iodide to an alkyl radical to initiate 1, n -hydrogen atom transfer. Unactivated secondary and tertiary C–H bonds at β, γ, and δ positions can be functionalized in a predictable manner.